Body image: differences and similarities between Colombian and Dutch teenagers - Ochoa Hoyos, Ana María (Perspectivas en Nutrición Humana, 2011)
<span style="font-size: 12.0pt; line-height: 115%; font-family: "Helvetica Narrow","sans-serif"; mso-fareast-font-family: "Times New Roman"; letter-spacing: 1.0pt; mso-font-kerning: 14.0pt; mso-fareast-language: ES-CO; mso-bidi-font-weight: bold;">Corrección al abstract publicado en el Vol. 9, Nº°2, 2007, p. 119